Preskok sistema plitve osnosimetrične bimetalne lupine z uporabo nelinearne teorije - Jakomin, Marko (Strojniški vestnik, 2006)
The paper deals with the stresses, strains and buckling conditions in thin, axially symmetric, shallow, bimetallic shells. Based on third-order theory, which takes into account the equilibrium state of the forces and moments that are acting on the deformed system, the paper presents a model with a mathematical description of the geometry of the system, the stresses, the thermoelastic strains and the displacements. The mathematical formulation is based on the theory of large displacements. As an example, the results for spherical, shallow shells are shown, approximated by a parabolic function. Besides simple roller-supported shells, also simple bearing-supported shells and clamped shells are discussed. The shells are loaded with temperature and/or a concentrated load acting at the top. The displacement state and the snap-through temperature are calculated numerically using a non-linear method.
Keywords: bimetalne lupine; termične lastnosti; mehanske lastnosti; matematični modeli